SAPS in the 17 March 2013 Storm Event: Initial Results From the Coupled Magnetosphere‐Ionosphere‐Thermosphere Model. Issue 7 (22nd July 2019) - Lin, Dong; Wang, Wenbin; Scales, Wayne A.; Pham, Kevin; Liu, Jing; Zhang, Binzheng; Merkin, Viacheslav; Shi, Xueling; Kunduri, Bharat; Maimaiti, Maimaitirebike
Abstract: Subauroral polarization stream (SAPS) is latitudinally narrow flow channels of large westward plasma drifts in the subauroral ionosphere. In this study, the global structure and dynamic evolution of SAPS are investigated by using the Coupled Magnetosphere‐Ionosphere‐Thermosphere model with ring current extension, namely, the Lyon‐Fedder‐Mobarry‐Thermosphere Ionosphere Electrodynamics General Circulation Model‐Rice Convection Model, to simulate the 2013 St. Patrick's Day storm event. This is the first time that the global distribution and temporal evolution of SAPS are investigated using first‐principle models. The model shows a strong westward ion drift channel formed equatorward of the auroral electron precipitation boundary on the duskside, which is identified as the SAPS structure. The simulated ion drift velocity and auroral electron precipitation sampled along the trajectory of the Defense Meteorological Satellite Program F18 satellite are in good agreement with the satellite measurements. SAPS initiate in the predusk sector when the interplanetary magnetic field turns southward. SAPS latitude generally decreases with magnetic local time from dusk to midnight. The SAPS channel shows wedge, inverse wedge, and crescent morphologies during the storm and becomes discontinuous when the interplanetary magnetic field is weakly southward. The SAPS mean latitude has a correlation coefficient of 0.77 with the Dst index. The mean latitude moves equatorward, and the flow channel broadens in the storm main phase. The simulation results illustrate both the global distribution and highly dynamic behavior of SAPS that are not readily apparent from the observation data. Key Points: SAPS is investigated with the Coupled Magnetosphere‐Ionosphere‐Thermosphere model with ring current extension SAPS global structures are characterized with the model and shown to be consistent with observations SAPS dynamic evolution and its dependence on the IMF B Z are quantitatively analyzed